CNB-001 a Novel Curcumin Derivative, Guards Dopamine Neurons in MPTP Model of Parkinson's Disease. (17th June 2014) - Jayaraj, Richard L.; Elangovan, Namasivayam; Manigandan, Krishnan; Singh, Sonu; Shukla, Shubha
Abstract : Copious experimental and postmortem studies have shown that oxidative stress mediated degeneration of nigrostriatal dopaminergic neurons underlies Parkinson's disease (PD) pathology. CNB-001, a novel pyrazole derivative of curcumin, has recently been reported to possess various neuroprotective properties. This study was designed to investigate the neuroprotective mechanism of CNB-001 in a subacute 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) rodent model of PD. Administration of MPTP (30 mg/kg for four consecutive days) exacerbated oxidative stress and motor impairment and reduced tyrosine hydroxylase (TH), dopamine transporter, and vesicular monoamine transporter 2 (VMAT2) expressions. Moreover, MPTP induced ultrastructural changes such as distorted cristae and mitochondrial enlargement in substantia nigra and striatum region. Pretreatment with CNB-001 (24 mg/kg) not only ameliorated behavioral anomalies but also synergistically enhanced monoamine transporter expressions and cosseted mitochondria by virtue of its antioxidant action. These findings support the neuroprotective property of CNB-001 which may have strong therapeutic potential for treatment of PD.